Distribution of ground-dwelling arthropods across landscapes with intensive agriculture in temperate areas. (July 2022) - Musters, C.J.M.; Wiggers, J.M.R.; de Snoo, G.R.
Highlights: Ground-dwelling arthropods were caught with pitfalls on fields in Illinois and The Netherlands. No effect of distance to (semi)natural area was found on the total abundance of arthropods. But the abundance of small arthropods decreased with distance in Illinois. We did find an effect of vegetation height and landscape complexity in both countries. The effect of nature conservation on ground-dwelling arthropods should be studied at large scales. Abstract: The idea that land use in the surroundings may affect the abundance of arthropods on a location plays an important role in the argument that agriculture is the prime cause of the recently discovered general decline of insects. We studied the abundance of ground-dwelling arthropods in agricultural fields along a gradient of increasing distance from (semi)natural areas and in relation to landscape complexity in both the North America (Illinois, USA) and Europe (The Netherlands) using pitfalls. Our results showed that the total abundance did not change with distance when we controlled for vegetation height and landscape complexity around the sample locations. Vegetation height affected abundance positively in crop land and negatively in grassland. Landscape complexity only affected abundance when it was measured in a 6000 m radius around sample location, not at lower levels of scale. We conclude that an effect of increasing landscape complexity may be expected when that is done on a large enough scale.